Factor Analysis of Physics Chemistry Waters that Affects Damage Safety Cliff on the Outskirts of River Siak - Marta Dinata; Fitridawati Soehardi (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2018)
This research to identify the physics chemistry vegetation of water on the outskirts of the Siak in terms of quality of the siak river good chemically, physics and biology and the erosion on a cliff the siak good use cliff safety and still in the original condition. This research is descriptive condition of vegetation of the safety of the cliff on coasts of siak river. Data needed is the on the results water quality measurement both in terms of physics, chemical and biological the oxygen dissolved, CO2 free, pH water, the speed of the current of a river, the sample water for measurements total suspended solid and the measurement of temperature water and BOD5. Of precipitation data required to count the intensity of rain and to approximate discharge flood on the siak river that occurs , and data safety conditions cliff coasts of siak river.Then analyzed in order so as to produce data that can identify physics chemistry factors waters that affects vegetation herbs coasts of siak river. The result of physics chemistry research identified factors waters that affects vegetation plants and damage a retaining wall land on the outskirts of the siak river ( case study kecamatan tualang siak district there are fatty oil luminance an observation station and she sulphate high category that ranged 239,50-341,87 mg/L . Followed by the womb klhorida 14,0-24,4 mg/L , phospat 5,31-5,83 mg/L. Organic substances contained in these waters make the acceleration of damage a retaining wall land on the outskirts of the river with the increase the number of this chemical was every mg/L . With pH values within the range 6,1-6,8 in addition to the womb of copper and lead contained in the quality of water made the vegetation that dominated the study areas this is the family of lythraceae and combretaceae that the average is the type of mangrove need phospat high. In the high number of this type of vegetation dominated the outskirts of the river, causing the wall safety a cliff on the outskirts of the river destroyed by aerial roots spread.